2000
DOI: 10.1097/00001756-200007140-00050
|View full text |Cite
|
Sign up to set email alerts
|

The face-specific N170 component reflects late stages in the structural encoding of faces

Abstract: To investigate which stages in the structural encoding of faces are reflected by the face-specific N170 component, ERPs (event-related brain potentials) were recorded in response to different types of face and non-face stimuli. The N170 was strongly attenuated for cheek and back views of faces relative to front and profile views, demonstrating that it is not merely triggered by head detection. Attenuated and delayed N170 components were elicited for faces lacking internal features as well as for faces without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

53
426
2
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 541 publications
(485 citation statements)
references
References 10 publications
53
426
2
4
Order By: Relevance
“…Since the trend found here is consistent with previous results which found significant differences between the N170 elicited by faces and human hands (e.g. Bentin et al, 1996;Eimer 2000, Onitsuka et al 2006, Kovacs et al 2006, and it was not the focus of the study, we did not investigated further the current null face-hands N170 effect.…”
Section: Resultssupporting
confidence: 90%
“…Since the trend found here is consistent with previous results which found significant differences between the N170 elicited by faces and human hands (e.g. Bentin et al, 1996;Eimer 2000, Onitsuka et al 2006, Kovacs et al 2006, and it was not the focus of the study, we did not investigated further the current null face-hands N170 effect.…”
Section: Resultssupporting
confidence: 90%
“…Following a similar time course, identity recognition progressively improved into late adolescence before reaching the adult level [73]. Thus face recognition may be a multi-stage process, where the early stage of face categorization is important for later stages of mnemonic processing that are sensitive to face identity [113,120,123].…”
Section: Erp Correlates Of Face Processing In Normal Adults and Childrenmentioning
confidence: 91%
“…Scalp ERPs and intracranial recordings from otherwise healthy epileptic patients have revealed a reliable and selective index of face processing at 150-200 ms latency, namely the scalp N170 [113][114][115]. Similarly, the intracranial N200, has been recorded at discrete locations over the fusiform gyrus, the inferior temporal sulcus (ITS) and the superior temporal sulcus (STS) [116].…”
Section: Erp Correlates Of Face Processing In Normal Adults and Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on face recognition using ERPs have demonstrated a difference in the ERPs to faces and objects at between 150-200 ms in bilateral occipito-temporal regions (Eimer, 2000;Rossion, Gauthier, Tarr, Despland, Bruyer, Linotte, & Crommelinck, 2000). Bentin, Allison, Puce, Perez, McCarthy (1996) investigated the response characteristics of the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 25 N170 using a target detection task in which various pictures of faces and other objects (e.g.…”
Section: Methodsmentioning
confidence: 99%